Changing nutrients, changing rivers - Ibáñez, Carles; Peñuelas, Josep (Science (American Association for the Advancement of Science), 2019)
Phosphorus removal from freshwater systems has wide-ranging ecological consequences Eutrophication—the excessive enrichment of a body of water with nutrients such as nitrogen (N) and phosphorus (P)—is Earth's most widespread problem for water quality ( 1 , 2 ). Growing evidence suggests a global trend toward reversing eutrophication. However, in rivers and estuaries of developed countries and in lakes of emerging economies, the ongoing reduction in nutrient inputs—termed reoligotrophication—is much larger for P than for N ( 3 , 4 ). Although the rapid emergence of this phenomenon has hindered detailed monitoring of the ecological effects, a few studies have documented an abrupt shift from green to clear waters and consequently from phytoplankton to macrophytes as dominant primary producers in response to reoligotrophication in rivers and estuaries ( 5 – 7 ). However, the improvement in water quality due to P decline does not imply a return to pristine ecological conditions, because high N:P ratios trigger undesirable changes in the ecosystem ( 8 ).